Appearance, Opinion, and Rhetoric in Aristotle - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 2006)
Various specialists of the Twentieth Century have recognized the important cognoscitive role that. Aristotle gave to opinion in the construction of knowledge. This paper shows that the diverse posed interpretations are about the discussion on how the retationship between opinion: (doxa) and appearance (phainomena) is understood or how the possible identification of them is grasped. Using these notions as a starting point, a proposal is made to see how Aristotle integrates them in his theory of rhetoric. Through a rhetortcal exercise the member of a determínate community deliberate, judge or recognize what is considered fair, convenient or worthy, when they, examine certain cases that are presented to their consideration. Rhetoric is presented as an art in, which opinion and appearance are combined. Through this art persuasion is brought on and a common experience is constructed (ways of seeing, of acting, or feeling) and in this way the polis is made